2008
DOI: 10.1029/2008gl035524
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pre‐existing oceanic conditions to upper ocean response induced by Super Typhoon Hai‐Tang

Abstract: [1] This study investigates upper ocean response to Super Typhoon Hai-Tang, the most intense typhoon in 2005, in the western North Pacific using multi-satellite microwave data, typhoon data and Argo profiles. Sequential merged microwave sea surface temperature (SST) images show that Hai-Tang induced four separately cooling responses after its trail in the western North Pacific during 11 -18 July.Comparison between upper ocean responses of cooling SST and pre-typhoon sea surface height suggests that these cooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 15 publications
8
86
4
Order By: Relevance
“…The physical mechanism primarily responsible for the increase in chl a concentration is the typhoon's strong wind, which induces mixing and upwelling in the upper ocean (Price 1981) and brings both subsurface chl a to the surface and subsurface nutrients into the euphotic zone (Subrahmanyam et al 2002, Lin et al 2003, Babin et al 2004, Zheng & Tang 2007, Gierach & Subrahmanyam 2008. Although it is not clear whether the extra chl a is due to the upwelling of nutrients or of chl a, we are sure that both the typhoon-induced upwelling and the pre-existing eddies favor the enhancement of chl a (Walker et al 2005, Shi & Wang 2007, Zheng et al 2008, McClain 2009, Sun et al 2009). The stronger the upwelling is, the more nutrients are transported to the surface.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The physical mechanism primarily responsible for the increase in chl a concentration is the typhoon's strong wind, which induces mixing and upwelling in the upper ocean (Price 1981) and brings both subsurface chl a to the surface and subsurface nutrients into the euphotic zone (Subrahmanyam et al 2002, Lin et al 2003, Babin et al 2004, Zheng & Tang 2007, Gierach & Subrahmanyam 2008. Although it is not clear whether the extra chl a is due to the upwelling of nutrients or of chl a, we are sure that both the typhoon-induced upwelling and the pre-existing eddies favor the enhancement of chl a (Walker et al 2005, Shi & Wang 2007, Zheng et al 2008, McClain 2009, Sun et al 2009). The stronger the upwelling is, the more nutrients are transported to the surface.…”
Section: Introductionmentioning
confidence: 93%
“…Although pre-existing oceanic conditions (cold core eddies) also play minor roles in ocean responses, they were often important in this respect in the upper ocean (Walker et al 2005, Shi & Wang 2007, Zheng et al 2008, Sun et al 2009). In fact, in some cases, cyclonic eddies became major contributors to sea surface cooling (Zheng et al 2008, Wada et al 2009. One large, cold core eddy appeared to be generated by typhoon wind forcing (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both anticyclonic warm core eddies (WCEs) and cyclonic cold core eddies (CCEs) can rapidly impact tropical cyclone (TC) intensity changes [e.g., Emanuel, 1999;Shay et al, 2000;Lin et al, 2005Lin et al, , 2009aWalker et al, 2005;Wu et al, 2007;Jaimes and Shay, 2009;Zheng et al, 2008Zheng et al, , 2010. Hurricanes Opal (1995), Katrina (2005), and Rita (2005) are examples of Gulf of Mexico TCs that intensified rapidly over areas of thick upper ocean warm layers [Shay et al, 2000;Jaimes and Shay, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…It intensified the preexisting CCE, producing one of the most energetic and long-lived cyclonic eddies in this ocean region over 16 years [Chelton et al, 2011]. Previous research has shown that TC-induced upwelling and mixing of nutrient-rich water from the upper thermocline can lead to an enhancement of Chla [Lin et al, 2003;Babin et al, 2004], especially within CCEs [e.g., Walker et al, 2005;Zheng et al, 2008]. In a study of 13 TC-induced phytoplankton blooms, Babin et al [2004] found that Chla values returned to prestorm levels within 2 to 3 weeks.…”
mentioning
confidence: 99%
“…The mean state of the climatological mixed-layer depth can be easily modified by eddies [19,20]. Cyclonic eddies uplift the subsurface temperature profile and thin the mixed-layer, while anti-cyclonic eddies push the isotherms downward and thicken the mixed-layer [12,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%